STUDENTS’ ASPIRATION, ATTRIBUTION, AND MOTIVATIONAL GOALS: A STUDY OF MINANGKABAU ETHNIC GROUP - Novita W. Sutantoputri; Juliana Murniati; Margaretha Purwanti (MANASA, 2014)
The study explored students’ aspiration, attribution, and motivational goals based on one ethnic group, Minangkabau. A total of 136 high school students from Minang ethnicity participated for the study. Students’ aspiration had three dimensions subscales: ambition, enjoyment of school life, and importance of school to the future. Attribution had three dimensions in the study: locus of control-personal control, stability, and external control. Students’ motivational goals had three dimensions: learning goals, performance approach goals and performance avoidance goals. The analyses show that importance of school aspiration and external control attribution predicted students’ learning goal. The present study gives an important view on how ethnicity should be considered in the study of students’ aspiration, attribution, and motivational goals, especially when one studies such variables in a multiethnic society.